The effect of working conditions on teachers' sickness absence - Marte Rønning (Statistics Norway, Research Department, 2012)
This paper investigates the effect of working conditions on the amount of teachers'sickness absence in Norway. Exploiting intertemporal variation within teachers who have not changed schools, the findings indicate that teachers lower their amount of sickness absence if the school's resource use increases. Increased workload and permanent employment contract are associated with higher sickness absence. When stratifying on teachers'age, increased workload appears to have a larger impact on old teachers.
Keywords: I10; I20; J28; 330; Teachers; absence; working conditions